An ionic liquid-present hydrothermal method for preparing hawthorn sherry ball shaped palladium (Pd)-based composite catalysts for ethanol oxidation reaction (EOR). (13th January 2020) - Ding, Keqiang; Han, Jingwei; Gao, Xiaojing; Wang, Li; Zhou, Lanjun; Qu, Runling; He, Xiangming
Abstract: For the first time, a hawthorn sherry ball shaped Pd-based composite catalyst for EOR was prepared via an ionic liquid-present two-step hydrothermal method in this work. In the first hydrothermal step, micron-scale solid carbon spheres (MSCS) were fabricated in the presence of glucose, an ionic liquid of 1-butyl-3-methyl tetrafluoroboric acid and one kind of surfactant. And in the second hydrothermal process, sesame like Pd particles were immobilized on the surface of MSCS forming a hawthorn sherry ball shaped Pd-based composite catalyst (denoted as Pd/MSCS) using PdO as the source of Pd. In the course of preparing MSCS, four kinds of surfactants were respectively employed desiring to study the influence of surfactant type on the physicochemical properties of the produced samples. The prepared MSCS and Pd/MSCS were examined majorly by X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). It was addressed by SEM images that in the presence of SDS and EDTA, hawthorn sherry ball shaped Pd-based composite catalysts were successfully prepared. XRD and XPS analysis substantially documented that metallic palladium was the main component of the synthesized Pd/MSCS catalysts. The electrocatalytic abilities of the Pd/MSCS catalysts for EOR were examined in 1 M C2 H5 OH alkaline solution mainly utilizing cyclic voltammetry (CV) and chronoamperometry (CA), illustrating that all produced Pd/MSCS catalysts had an electrocatalytic activity towards EOR, and the forward peak current density of EOR on the catalyst of Pd/MSCS (prepared in the presence of SDS) was 7 times larger, along with 60 mV decrease in the onset potential of EOR, than that on the Pd/MSCS (prepared with CATB) catalyst. Summarily, a very cost-effective and facile method for fabricating hawthorn sherry ball shaped Pd-based composite catalysts towards EOR was created in this work, which was very meaningful not only to the further development of EOR catalysts but also to the exploration of micron-devices. Graphical abstract: A hawthorn sherry ball shaped Pd-based composite catalyst for EOR was prepared via an ionic liquid-present two-step hydrothermal method. And it was revealed that the kind of surfactant was an important factor affecting both the carbon spheres size and the surface morphologies of the resultant carbon spheres, as well as the electrocatalytic activities of the prepared catalysts towards EOR. Image 1 Highlights: Micron-scale solid carbon spheres (MSCS) (>6 μm) were prepared by an ionic liquid-present hydrothermal method. Hawthorn sherry ball shaped Pd/MSCS were produced using MSCS and PdO as the starting materials. Pd/MSCS prepared with SDS delivered the best electrocatalytic activity for EOR.